КЛИНИЧЕСКОЕ ТЕЧЕНИЕ И ИСХОДЫ ХРОНИЧЕСКОЙ ДЕЛЬТА-ИНФЕКЦИИ В ЭНДЕМИЧНОМ РЕГИОНЕ - Л. Ю. Ильченко; Т. В. Кожанова; А. А. Сарыглар; Я.-Н. Д. Сонам-Байыр; О. Н. Сарыг-Хаа; Р. М. Соян; Ю. П. Зубков; О. В. Исаева; К. К. Кюрегян; М. И. Михайлов (Архивъ внутренней медицины)
Total 214 patients with delta infection were examined. Total 48 patients were followed annually during the observation period (2009–2011). Diagnosis of chronic hepatitis delta (CHD) was established in 78,6% (162/206) cases, liver cirrhosis (LC) — in 21,4% (44/206). HDV RNA was detected in 26,2% (56/214) patients. HDV was genotype I. Progression of CL was observed among 31,3% (15/48) of followed patients, decompensation of CL — in 8,3% (4/48), hepatocellular carcinoma — in 4,2% (2/48) cases; mortality was 29,2% (14/48), with hepatic coma and bleeding from esophageal varices as the main cause of death.